Awareness about Mental Illness among the Family Members of Psychiatric Patient attending Psychiatric Outpatient Department of Bharatpur Hospital - Lamichhane, Rama Kumari; Thapa, Asha; Dhakal, Bijaya; Regmi, Kamala; Adhikari, Pratima (Journal of Bharatpur Hospital, 2025)
Background: Mental health issues have emerged as a significant concern in today’s landscape. It is crucial for family members to be aware of mental illness to provide effective care for their loved ones at home. Awareness plays a key role in the early detection of mental health problems. This study seeks to assess the level of awareness of mental illness among the family members of psychiatric patients. Methods: This study utilized a cross-sectional research design to assess the awareness of mental illness among the family members of psychiatric patients visiting the Psychiatric Outpatient Department of Bharatpur Hospital from August to December, 2024. A non-probability purposive sampling technique was employed to select the sample, which consisted of 325 family members. A self-constructed, structured questionnaire was used to interview the participants and evaluate their level of awareness. Chi-square analysis performed to examine the association between demographic variables and level of awareness with a significance level set at p < 0.05. Results: Among 325 family members, 306 (94.15%) had heard about mental illness, of these, 164 (53.6%) of the respondents had poor level of awareness. No significant association was found between level of awareness and sociodemographic variables of the participants. Conclusions: The Study revealed that more than half of the respondents had poor level of awareness about mental illness. These finding highlight the need for targeted interventions to improve awareness among family members, which could contribute to better management of psychiatric patients.